(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This scientific article examines the effectiveness of combined preventive measures involving hormonal therapy and lifestyle modifications in women diagnosed with Polycystic Ovary Syndrome (PCOS). The study focuses on the role of integrated preventive strategies in improving reproductive, metabolic, and hormonal outcomes in affected women. The findings indicate that hormonal therapy contributes to the regulation of menstrual cycles and reduction of hyperandrogenic manifestations, while lifestyle modifications—including balanced nutrition, regular physical activity, weight control, and behavioral changes—significantly improve insulin sensitivity and metabolic parameters. The results demonstrate that the combined application of hormonal treatment and lifestyle interventions is more effective than single-modality approaches in preventing disease progression and reducing the risk of long-term complications. Based on the obtained results, the implementation of comprehensive, individualized preventive programs is recommended to improve health outcomes and quality of life in women with PCOS.